2010
DOI: 10.1029/2010ja015458
|View full text |Cite
|
Sign up to set email alerts
|

On the reformation at quasi‐ and exactly perpendicular shocks: Full particle‐in‐cell simulations

Abstract: [1] A full particle-in-cell (PIC) simulation study is carried out on the reformation at quasi-and exactly perpendicular collisionless shocks with a relatively low Alfven Mach number (M A = 5). Previous self-consistent one-dimensional (1-D) hybrid and full PIC simulations have demonstrated that ion kinetics are essential for the nonstationarity of perpendicular collisionless shocks. These results showed that reflection of ions at the shock front is responsible for the periodic collapse and redevelopment of a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 25 publications
(64 reference statements)
1
23
0
Order By: Relevance
“…Moreover, the shock-reformation process can also be influenced by the shock-front ripples. The latter was shown to modify the period of the reformation cycles in later stages in low-Mach-number perpendicular shocks (e.g., Hellinger et al 2007;Lembège et al 2009;Umeda et al 2010). However, the rippling of the shock surface is weak in our case of a high-Mach-number forward shock and we do not see any apparent change of the reformation period throughout the duration of our simulation.…”
Section: Shock Reformationmentioning
confidence: 51%
See 2 more Smart Citations
“…Moreover, the shock-reformation process can also be influenced by the shock-front ripples. The latter was shown to modify the period of the reformation cycles in later stages in low-Mach-number perpendicular shocks (e.g., Hellinger et al 2007;Lembège et al 2009;Umeda et al 2010). However, the rippling of the shock surface is weak in our case of a high-Mach-number forward shock and we do not see any apparent change of the reformation period throughout the duration of our simulation.…”
Section: Shock Reformationmentioning
confidence: 51%
“…For panel (b), we compensated the average velocity of all ions (see Figure 10), whereas for panel (c) on the right we compensated only the average motion of incoming ions. Umeda et al 2009Umeda et al , 2010Umeda et al , 2014. The ion temperature anisotropy arising from ion reflection at the shock can drive the Alfvén ion cyclotron (AIC) or the mirror instability in the shock ramp, and the resulting unstable modes have wavelengths of a few ion skin depths and propagate along the regular magnetic field, significantly contributing to ion isotropization and thermalization at the shock and downstream.…”
Section: Structure Of the Reverse Shockmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2-D hybrid simulations of Yuan et al (2009), on the other hand, seemed to show that reformation could occur despite the presence of whistler waves. However, it has been shown that reformation can appear to be suppressed if quantities are averaged over a direction tangential to the shock surface, even though the time evolution at a fixed point on the shock surface does show oscillations attributed to reformation (Umeda et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In order to study the contradiction between the former (Hellinger et al, 2007;Lembege et al, 2009) and latter (Yuan et al, 2009) results, a direct comparison was made between the 2-D full PIC simulation results of quasi-perpendicular (θ B n = 80 • ) and exactly perpendicular (θ B n = 90 • ) shocks (Umeda et al, 2010). It was confirmed that the shock-normal angle does not affect the presence or the suppression of the reformation of (quasi-)perpendicular shocks.…”
Section: Introductionmentioning
confidence: 97%